2017
DOI: 10.1016/j.jeurceramsoc.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Compact hollow fibre reactors for efficient methane conversion

Abstract: In this study, a micro-structured catalytic hollow fiber membrane reactor (CHFMR) has been prepared, characterized and evaluated for performing steam methane reforming (SMR) reaction, using Rh/CeO2 as the catalyst and a palladium membrane for separating hydrogen from the reaction. Preliminary studies on a catalytic hollow fiber (CHF), a porous membrane reactor configuration without the palladium membrane, revealed that stable methane conversions reaching equilibrium values can be achieved, using approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The fibers were sequentially dipped in the sensitization-activation baths of SnCl2 for 5 min, deionized water for 5 min, PdCl2 for 5 min, HCl for 2 min, and deionized water for 3 min. Air was bubbled in all baths to ensure a homogenous deposition of palladium seeds on the fiber surface, as suggested by Prasetya et al [13] . This sensitization--activation treatment was repeated 5 to 8 times until the surface of the fiber was dark brown.…”
Section: Methodsmentioning
confidence: 99%
“…The fibers were sequentially dipped in the sensitization-activation baths of SnCl2 for 5 min, deionized water for 5 min, PdCl2 for 5 min, HCl for 2 min, and deionized water for 3 min. Air was bubbled in all baths to ensure a homogenous deposition of palladium seeds on the fiber surface, as suggested by Prasetya et al [13] . This sensitization--activation treatment was repeated 5 to 8 times until the surface of the fiber was dark brown.…”
Section: Methodsmentioning
confidence: 99%
“…7(b)), silver and titanium were mainly observed on the ber external surface, although some particles were also observed throughout the ber cross-section Prasetya et al (2017). showed the proper deposition of Rh/CeO 2 catalysts inside the microchannels of asymmetric alumina hollow bers.…”
mentioning
confidence: 88%
“…recirculation, generation of preferential paths and stagnant regions), and (iii) mass transfer, resulting in improved reaction kinetics. 5,53,54 Fig. 5B schematically represents that the use of a HFC avoids the diffusion limitations typically associated with a PBR, which are caused by the tortuosity, porosity and constriction factor of the porous structure of the catalyst pellets.…”
Section: Performance Studies Of the Hollow Bre Converter During The ...mentioning
confidence: 99%
“…3 Indeed, it has been demonstrated that the use of HFRs narrows the residence time distribution and decreases the catalyst loading and/or the operating temperatures when compared with traditional PBRs. [3][4][5] Moreover, they exhibit an exceptional area/volume ratio without compromising the pressure drop and efficiency. Furthermore, HFRs offer the advantage of improved reaction kinetics due to minimised internal and external diffusion limitations, thereby enhancing the viability of using nonprecious metal-based catalysts.…”
Section: Introductionmentioning
confidence: 99%